The relationship between gut microbiome estrobolome and breast cancer: A systematic review of current evidences - Mahno, Noor Ezmas; Tay, Darren Dean; Nurul Syazwani, Khalid; Aini Syahida, Mat Yassim; Nor Syuhada, Alias; Sahrol Azmi, Termizi; Junaini, Kasian; Norfilza, Mohd Mokhtar; Hajar Fauzan, Ahmad (Springer, 2023)
Breast cancer is the most frequent kind of cancer and the second leading cause of mortality worldwide, behind heart disease. Next-generation sequencing technologies enables for unprecedented enumeration of human resident gut microorganisms, conferring novel insights into the role of the microbiota in health and individuals with breast cancer. A growing body of research on microbial dysbiosis seems to indicate an elevated risk of health complications including cancer. Although several dysbiosis indices have been proposed, their underlying methodology, as well as the cohorts and conditions of breast cancer patients are significantly different. To date, these indices have not yet been thoroughly reviewed especially when it comes to researching the estrogen-gut microbiota axis. Instead of providing a thorough rating of the most effective diversity measurements, the current work aims to be used to assess the relevance of each study's findings across the demographic data, different subtypes, and stages of breast cancer, and tie them to the estrobolome, which controls the amount of oestrogen that circulates through humans. This review will cover 11 studies which will go into a detailed discussion for the microbiome results of the mentioned studies, leaving to the user the final choice of the most suited indices as well as highlight the observed bacteria found to be related to the estrobolome in hopes of giving the reader a better understanding for the biological cross-talk between gut microbiome and breast cancer progression.